Tangibilidade e intangibilidade na determinação do desempenho superior e persistente de firmas brasileiras - Carvalho, Francisval de Melo (2009)
RBV advocates that resources and competencies be distributed heterogeneously among firms of a determined industry, therefore, being the main cause of the variation observed in the performance of companies. When these resources are rare, valuable or difficult to be imitated and the firm disposes of an adequate organizational structure to explore them, they have the potential to promote the superior and persistent performance of the company. By using the model adapted from Villalonga(2004), the present paper had as its initial objective to evaluate if the superior and persistent performance of the firms have any relationship to the intangibility of its resources. Also verified in the following stage, was if the superior and persistent performance of the companies was influenced by the variation of the tangibility of its resources. The companies performance was measured by the specific profit of the firm (LEF), calculated by the difference between the return on assets (ROA) of the firm and the average value of ROA of the sector of the economy of which the company is part of. Superior performance indicated that the firm presented LEF above the average of the sector and persistent performance signaled that the superior performance was maintained in the long run. The intangibility of resources was measured by the Q of Tobin and the tangibility by the PL variation. The sample was composed of open capital brazilian companies, whose stocks were listed in the BOVESPA and by information accessed through Economática® Consultoria s database. The statistic techniques that were used were multivariable regressions using the Minimal Ordinary Squares (MQO) method, analysis of statistic panels with estimates nonvariable effects (EF) and random effects (EA) and dynamic panel with estimates by the Generalized Moments method (GMM). The main results found suggests that for the brazilian reality, the intangibility of resources is a factor that contributes to the above average performance of the firms, however, this influence is perceptible in a positive and significant way in few sectors of the economy. Even though contributing to superior performance, the intangibility of the assets, didn t reveal itself as a sustainable competitive advantage, due to the observation that these resources didn t contribute to the persistence of superior performance of the firms, differing therefore, from the results obtained in other studies. Static evidence exists that the variation of tangible resources has importance to explain the above average performance of brazilian firms, however, a very variable influence is perceived among the sectors of the economy. Besides contributing to a superior performance, the tangibility of resources can be considered as a competitive sustainable advantage, having contributed in a significant manner to superior performance sustainability of the firms of diverse sectors of the economy.